Liddle disease caused by a missense mutation of beta subunit of the epithelial sodium channel gene. - Tamura, H (1996)
Mutations in beta or gamma subunit of the epithelial sodium channel (ENaC) have been found to cause a hereditary form of human hypertension, Liddle syndrome. Most of the mutations reported are either nonsense mutations or frame shift mutations which would truncate the cytoplasmic carboxyl terminus of the beta or gamma subunits of the channel, suggesting that these domains are important for the normal regulation of this channel. We sequenced ENaC in a family with Liddle syndrome and found a missense mutation in beta subunit which predicts substitution of Tyr by His at codon 618, 2 bp downstream from a missense mutation (P616L) that has been reported recently. Presence of this mutation correlates with the clinical manifestations (hypertension, hypokalemia, suppressed aldosterone secretion) in this kindred. Functional expression studies in the Xenopus oocytes revealed constitutive activation of the Y618H mutant indistinguishable from that observed for the deletion mutant (R564stop) identified in the original pedigree of Liddle. Our data suggest that the region between Pro616 and Tyr618 is critically important for regulation of ENaC activity.